2022
DOI: 10.21608/bmfj.2022.109333.1518
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Microbial Factors Affecting Culture of Helicobacter Pylori

Abstract: Background: Helicobacter pylorus has been identified as a major cause of peptic ulcer disease, risk factor for gastric cancer and mucosa associated lymphoid tissue (MALT) lymphoma. There is an emerging increase in antimicrobial resistance and subsequently failing empiric H. pylori eradication therapies which increases need to asses antibiotic susceptibility for H. pylori in every country, this will be done after its culture. Culturing of H. pylori is affected by multiple factors. Aim of the work: To Identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…As observed in the majority of studies, Columbia blood agar is the most commonly used culture medium for isolating H. pylori, despite its limited culture sensitivity (44.1%) as provided by Al-Sulami et al (2008). Furthermore, Ragab et al (2022) found that the sensitivity of the culture method for detecting H. pylori was comparatively low at 16.5%, as opposed to histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in the majority of studies, Columbia blood agar is the most commonly used culture medium for isolating H. pylori, despite its limited culture sensitivity (44.1%) as provided by Al-Sulami et al (2008). Furthermore, Ragab et al (2022) found that the sensitivity of the culture method for detecting H. pylori was comparatively low at 16.5%, as opposed to histopathology.…”
Section: Introductionmentioning
confidence: 99%